2019
DOI: 10.5935/abc.20190134
|View full text |Cite
|
Sign up to set email alerts
|

Presystolic Wave is Associated with Subclinical Left Ventricular Dysfunction Assessed by Myocardial Performance Index in Type 2 Diabetes Mellitus

Abstract: BackgroundMyocardial performance index (MPI), demonstrates both systolic and diastolic functions of the left ventricle. Presystolic wave (PSW) is frequently detected on Doppler examination of the left ventricular outflow tract and possible mechanism of PSW is impaired LV compliance and left ventricular stiffness.ObjectiveTo investigate the relationship between PSW and MPI in type 2 diabetic patients.MethodA total of 129 type 2 diabetic patients were included in this study. Patients were divided into two groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
2
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 33 publications
0
13
2
1
Order By: Relevance
“…The prevalence of the PSW was the same in subjects with and without common atherosclerotic risk factors (eg, DM, HTN, DLP, and smoking). In another study on 129 patients with DM type 2, the prevalence of PSW was 69.8% (90/129), which was higher than the findings of our study (49.1%) 17 . EF was lower than 50%, in 55.5% of the patients, while in the mentioned study, the mean EF was above 60% which might explain the lower prevalence of the PSW in our study 17 …”
Section: Discussioncontrasting
confidence: 85%
See 2 more Smart Citations
“…The prevalence of the PSW was the same in subjects with and without common atherosclerotic risk factors (eg, DM, HTN, DLP, and smoking). In another study on 129 patients with DM type 2, the prevalence of PSW was 69.8% (90/129), which was higher than the findings of our study (49.1%) 17 . EF was lower than 50%, in 55.5% of the patients, while in the mentioned study, the mean EF was above 60% which might explain the lower prevalence of the PSW in our study 17 …”
Section: Discussioncontrasting
confidence: 85%
“…In another study on 129 patients with DM type 2, the prevalence of PSW was 69.8% (90/129), which was higher than the findings of our study (49.1%). 17 EF was lower than 50%, in 55.5% of the patients, while in the mentioned study, the mean EF was above 60%…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…Joshi KR et al 20 have found that the absence of PSW is associated with increased frequency of adverse event and one study have shown that PSW is an indicator of impaired compliance of LV 21 . Kul S. et al 22 have found that PSW is associated with subclinical LV diastolic dysfunction in patients with DM. Akyuz AR et al 23 have detected that PSW is an independent predictor of subclinical LV dysfunction in patients with HT.…”
Section: Discussionmentioning
confidence: 98%
“…Presystolic wave (PSW) measurement is obtained via doppler examination of LV outflow tract (LVOT). 5,6 Kul et al 7 found that the PSW is associated with subclinical LVDD in patients with type 2 diabetes. PSW is an easily measurable echocardiographic parameter obtained in late diastole and can predict subclinical left ventricular dysfunction in patients with type 2 diabetes.…”
mentioning
confidence: 99%